Modeling of clustering and spread of diseases with multidrug pathogens - Ільницький, Г.І.; Ільницький, Я.М. (Science-based technologies, 2015)
The epidemiology model for the non-immune disease with both ordinary and multi drug resistant carriers tuberculosis is considered via cellular automata algorithm on a square lattice. The early stage and stationary state of the disease are studied in various epidemiology regimes, as well as relative prevalence of multi drug resistant carrier, spatial patterns and clusterisation of infected individuals.